Partisipasi Masyarakat Lokal Dalam Pengembangan Daya Tarik Wisata Pantai Melasti, Kabupaten Badung, Bali - Marbun, Usy Anggre Yuni; Adikampana, I Made; Narottama, Nararya (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p10, 2023)
Melasti beach was one of the attractions of tourism located in Badung Regency and implemented the development of community based tourism. The development of a tourist attraction urgently requires the participation of local communities. Thus, the study aims to analyze the participation of local communities in the development tourist attraction Melasti Beach must act by indentifying the typology of community participation, the push and obstacle participation factors and then creating a strategy to enchance community participation. The study uses qualitative descriptive analysis techniques that refer to the typology of local community participation that has been identified. The collection of data in this study is observation, interview and documentation. The result of the study suggest that improved Melasti Beach development positions are expected at the stage of development and that type community participation is induced participation. After analysis of what contributed to community participation in the high interest rates on the coast of Melasti, communities began to fell the economic impact from activities of tourism and development and management based on community. As a result of the lack of awareness of local communities as a local investor in the development of local tourist attraction and torism participants began to be dominated by the local elit. Keywords: Community Participation, Typology of Participation, Community Based Tourism, Tourist Attraction, Melasti Beach, Tourism Development